Avaliação de fitas de magnésio, com ou sem revestimento de fosfato de cálcio, e sua influência na viabilidade, proliferação e ativação de osteoblastos murinos, além da biocompatibilidade em dorso de ratos wistar - Veras, Mariana de Oliveira Viana (2021)
Biomaterials for bone grafting are used as scaffolds to promote the osteogenesis process in cases where physiological mechanisms are not sufficient to repair tissue damage. Several academic studies carried out in order to seek techniques and adequate bone substitutes. Therefore, the objective of this study was evaluate the effect of magnesium (Mg1) and Mg tapes coated with calcium phosphate (Mg2), developed and characterized by our research group, on the viability and activation of murine osteoblasts in vitro, as well as their biocompatibility through its application on the back of Wistar rats. Cell viability and proliferation were assessed using the MTT and MTS assay, respectively, after 24 and 48 hours of osteoblast incubation with magnesium tapes. Quantification of bone alkaline phosphatase (FAO) levels in the culture medium after 24 hours, 7 and 15 days of incubation was one of the parameters used to investigate osteoblast activity, in addition to the mineralization assay by Von Kossa staining, after 21 cell culture days. Cell morphology and death were also investigated by fluorescence optical microscopy and immunostaining for caspase 3 and 9, respectively. For the investigation of the mechanisms involved in cell activation, the protein expressions of BMP-2, OPG and RANK-L were investigated by immunostaining. In in vivo studies, for the evaluation of biocompatibility, the inflammatory response induced by the implantation of the tapes on the back of Wistar rats was investigated at different observation times, considering the infiltration of inflammatory cells around the site occupied by the biomaterial, and area and number of the vessels blood. The results showed that after 24 and 48 hours of incubation, a significant increase in the number of viable cells was observed in the Mg1 and Mg2 groups. The MgF group presented more intense mineralization compared to the Control and Mg groups, in addition to a significant increase in FAO activity. Cells cultured on both types of magnesium tape generate greater expression of BMP-2 and OPG, compared to cells cultured without the presence of biomaterial. There was no difference in the expression of RANK-L between the three groups. As Mg2 tapes, biocompatibles are differentiated. The results obtained a positive effect of Mg1 and Mg2 tapes on the proliferation, viability and participation of osteoblasts, with BMP-2 and OPG. The association of in vitro data and biocompatibility found in the in vivo study, strongly strongly with the use of biomaterial in the regeneration of bone defects, especially basic defects.